A brand Identity for the Parish of Nossa Senhora de Fátima (in Lisbon) - Rocha, Lígia Cristina Castanheira (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics